THE ENGLISH COMPETENCE OF FRONT OFFICE HOTEL PERSONNEL - Rindang Widiningrum (Universitas Stikubank (UNISBANK) Semarang, 2010)
A hotel is a place for many people who are away from home for many kinds of reasons, such as meeting, pleasure, seminar, and shopping. Many of these people are foreigners of different nations, who communicate mainly in English. When they need a place to stay, they will find a hotel, and the first people they communicate with are the front office personnel. This study was conducted to answer one research question: What English competence is required of hotel front office personnel? This was qualitative research within the aim to find the communicative competence of front office personnel. To get the data, the researcher conducted interview and also asked the participant to fill in the questionnaires. The research result showed that the front office personnel must be competence in the four skills to communicate with the gueats because they were the first persons to interact with the guests. Each skill has its own required competence based on the participant’ behavior, opinion, and feeling. Key words: English communication, English competence, front office personnel.